Role of Regulation in Driving Educational Transformation Based on Organizational Reform Government - Ernia Duwi Saputri; Sely Ayu Lestari (Proceeding International Conference on Digital Education and Social Science, 2024)
System education can adapt with changing times, overcoming challenges , and fulfill need public in a way sustainable If the regulation right . If the regulation designed in a way participatory and implemented with commitment height , transformation education will become more effective and inclusive . In the research This discuss related to what extent regulation support change in Education system and relations between organizational reforms government with Education. Research This is type study qualitative descriptive Because focus on understanding related role regulation and transformation process of Education in context of organizational reform government . Regulation is mover in transformation education , especially when accompanied by with organizational reform adaptive governance . With​ proper regulation and its consistent implementation , education​ can become tool For create a smart , inclusive and sustainable society